A implementação dos serviços de enfrentamento à violência sexual de crianças e adolescentes no âmbito da Política Nacional de Assistência Social-PNAS/SUAS: limites e possibilidades de atuação - Caldas, Paula da Silva (2014)
The present research that based this thesis has the objective to do the analysis on the process of implementation of the Coping With Sexual Services for Children and Adolescents. This territorial focus is the city of Rio de Janeiro after the new conception of the social policy based on the Single System of the Social Assistance SUAS, and its structures on the program of Protection Service and Specialized Care for Families and Individuals - PAEFI. For development of this research, we did semi-structured interviews with technicians and managers whom acts on these services the coping with sexual services for children and adolescents, even with the managers from the administration area of the Municipal Secretary of Social Development of Rio de Janeiro SMDS. We used some informations from the reports of this Secretary that provided us with a more thorough analysis above the interfamily violence against children and adolescents. This analysis provided us the conclusion that despite the advances generated from this new conception of SUAS like a public policy, the coping with sexual services for children and adolescents on the PAEFI prospects, it still need an upgrading on its managers, execution and monitoring basis, knowing the difficult on doing a familiar accompaniment on an effective way, the same way that need to create strategies and tool to coping the children and adolescent sexual exploration, with a integrate articulation of all the actors from the Guarantee Rights System SGD